The Role of Consent and Motivations in Sext Dissemination - Clancy, Elizabeth M. (Journal of interpersonal violence, 2023)
Sext dissemination (i.e., the online sharing of sexually explicit images) has the potential to result in legal, social, and psychological harms. Recent research has shown that this behavior can be consensual or non-consensual in nature; yet little is known about how motivations or attitudes may differ between these forms, or with gender. This study is based on a cross-sectional online survey investigating consensual and non-consensual sext dissemination and associated demographic, behavioral, attitudinal, and psychological factors. Participants were 2,126 cisgendered adults aged 18 to 30 years (M = 22.97, SD = 3.21, 55% women, 45% men), resident in Western, English-speaking nations, particularly Australia. Around 10% of respondents reported disseminating texts, and of these, only 19.8% indicated they had permission for this, with no differences across gender. When sexts were disseminated “to gossip,” this was significantly more likely to be non-consensual. There were no significant differences between consensual and non-consensual dissemination in subjective attitudes or norms toward dissemination, nor levels of psychological distress. Women were more likely to non-consensually disseminate sexts that had been received as unwanted or unwelcome. Consensual dissemination was weakly associated with being sexually active and having given consent to having one’s own images disseminated. We discuss implications for future research regarding consent, and relationship and sexuality education.